Determinant of Indonesian Islamic Banks Liquidity Risk - Dwi Arfiyanti; Imanda Firmantyas Putri Pertiwi (Profesional Muda Cendekia Publishing, 2020)
An assessment of the liquidity of a bank is one way to determine whether the bank is in good health, fairly healthy, and unhealthy. This study aims to analyze the influence of the company's internal factors consisting of Return on Assets, Capital Adequacy Ratio and Bank Size on the liquidity ratio as measured by using two proxies, namely Liquid Asset to Total Asset (LATA and Financing Deposi Ratio (FDR). This study uses Islamic banks as the object of research in the 2014-2018 period. The results of data analysis using panel data regression showed that ROA and CAR had no effect on liquidity risk. Meanwhile, bank size has a significant negative effect on the liquidity ratio using LATA and FDR